Introduction to the ribosome - Liljas, Anders (Henry Stewart Talks, 2008)
The understanding of heredity and translation of proteins based on the genetic information, Intensive structural studies of ribosomes, tRNAs and translation factors, A historical overview, Main components of translation
Archived at 2020/08/13